Magnetorheological fluid with magnetorheological property and stability, preparation method and application thereof
Patent Information
- Application Number
- CN202611256968.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
为此,本发明的主要目的在于提供一种沉降率低、零场粘度低、剪切屈服应力高的磁流变液体,旨在解决现有磁流变液沉降稳定性差、磁流变性能与抗沉降性能难以兼顾的问题
1)本发明所提供的磁流变液中,通过聚多巴胺的强粘附性实现与磁性颗粒基底的牢固结合,同时利用聚多巴胺分子表面丰富的氨基、羟基作为活性位点,实现聚异丁烯丁二酸酐的稳定接枝,形成“磁性颗粒基底-聚多巴胺桥连层-聚异丁烯丁二酸酐接枝层”的核壳结构改性颗粒,二者协同改性羰基铁粉,既保证改性颗粒的磁性能,又提升其抗沉降性;
Smart Images

Figure CN122991797A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of smart materials technology, specifically relating to a magnetorheological fluid with both magnetorheological properties and stability, and its preparation method; more specifically, it relates to an anti-settling magnetorheological fluid prepared by grafting carbonyl iron powder with polydopamine as a bridging agent and polyisobutylene succinic anhydride as a surfactant, and its preparation method. It can be widely used in vehicle vibration reduction, precision machinery, medical equipment and other fields, and is especially suitable for scenarios with high requirements for the sedimentation stability and magnetorheological performance of magnetorheological fluids. Background Technology
[0002] The statements in this section are merely background information related to the present invention and do not necessarily constitute prior art.
[0003] Magnetorheological fluid is a smart composite material composed of magnetic particles, base fluid and additives. It is a flowing liquid when there is no magnetic field, but can be transformed into a solid-like state within milliseconds after a magnetic field is applied. Its rheological properties can be continuously controlled by the magnetic field strength. This unique magnetic response characteristic makes it have broad application prospects in vibration control, precision polishing, sealing and vibration reduction, and auxiliary medical treatment.
[0004] Currently, the most commonly used magnetic particles in magnetorheological fluids are carbonyl iron powder, which has high saturation magnetization and permeability, giving magnetorheological fluids excellent magnetorheological effects. However, carbonyl iron powder has a high density, and the density difference with the base fluid is significant. This causes magnetic particles to settle and agglomerate easily during long-term standing, which seriously affects the service life and performance of the magnetorheological fluid. This problem has become a key bottleneck restricting the large-scale engineering application of magnetorheological fluids.
[0005] To address the sedimentation problem of magnetorheological fluids, existing technologies mainly employ two approaches: one is to add additives such as thixotropic agents and nanoparticles to construct a three-dimensional network structure that hinders the sedimentation of magnetic particles. However, the addition of a large number of additives can lead to an increase in the zero-field viscosity of the magnetorheological fluid, reducing its magnetic field response speed. The other approach is to modify the surface of the magnetic particles by coating the particle surface with organic or inorganic substances to improve the compatibility between the particles and the base fluid, reduce the density difference, and at the same time, utilize the steric hindrance effect to prevent particle aggregation.
[0006] Surface modification is one of the most effective means to improve the sedimentation stability of magnetorheological fluids. Commonly used modifiers include surfactants, polymers, and inorganic nanomaterials. Among the commonly used surfactants are sodium dodecylbenzenesulfonate and stearic acid. Although they can improve particle compatibility to some extent, they have limited effect on improving the sedimentation stability of the modified magnetorheological fluid and tend to lead to a decrease in magnetorheological properties. They cannot effectively solve the problems of poor sedimentation stability and difficulty in balancing magnetorheological properties and anti-settling properties in existing magnetorheological fluids. Summary of the Invention
[0007] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide a magnetorheological fluid with low sedimentation rate, low zero-field viscosity, and high shear yield stress, thereby addressing the problems of poor sedimentation stability and the difficulty in simultaneously achieving magnetorheological properties and anti-sedimentation properties in existing magnetorheological fluids.
[0008] The present invention also provides a method for preparing the magnetorheological fluid; The present invention also provides the application of the magnetorheological fluid in vehicle vibration damping systems, precision polishing equipment, and sealing devices.
[0009] The objective of this invention is achieved through the following technical solution: A magnetorheological fluid that combines magnetorheological properties and stability comprises the following components by weight percentage: 70-85% dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder, 12-22% base liquid, and 2-9% additives.
[0010] In some specific embodiments, the dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder is prepared by the following method: S1. Surface activation: Carbonyl iron powder is dispersed in ethanol, ultrasonically treated for 10-30 min, magnetically separated and dried to obtain surface-activated carbonyl iron powder; S2. Dopamine-bridged coating: The surface-activated carbonyl iron powder in S1 was added to Tris-HCl buffer solution and stirred evenly. Then, dopamine solution was added dropwise to adjust the pH of the system to 8.0-9.0. The reaction was stirred at 25-35℃ for 12-24 hours. After magnetic separation, washing and drying, polydopamine-coated carbonyl iron powder was obtained. In this step, the self-polymerization reaction of dopamine forms hydrogen bonds and covalent bonds with the hydroxyl groups on the surface of carbonyl iron powder, constructing a dense polydopamine bridging layer, which provides active sites for subsequent grafting of polyisobutylene succinic anhydride. S3. Polyisobutylene succinic anhydride grafting: Polydopamine-coated carbonyl iron powder is added to an organic solvent, polyisobutylene succinic anhydride is added, and the mixture is stirred at 60-80℃ for 4-8 hours. After cooling, it is magnetically separated, washed, and dried to obtain polydopamine-bridged-polyisobutylene succinic anhydride grafted modified carbonyl iron powder. In this step, the succinic anhydride groups of polyisobutylene succinic anhydride undergo an amidation reaction with the amino groups of the polydopamine bridging layer to achieve grafting, and the long-chain polyisobutylene groups extend outward to form a steric hindrance layer.
[0011] In some specific embodiments, the polyisobutylene succinic anhydride in this invention needs to have excellent compatibility with the base liquid. Simultaneously, its long-chain polyisobutylene groups provide steric hindrance to prevent the agglomeration of modified carbonyl iron powder. Furthermore, the succinic anhydride groups form chemical bonds with the amino and hydroxyl groups of the polydopamine bridging layer, achieving strong anchoring and improving grafting stability. Therefore, the polyisobutylene succinic anhydride in this invention has a number-average molecular weight of 1000–5000 and a hydrophilic-lipophilic balance value of 3–8. The carbonyl iron powder is spherical with an average particle size of 1–10 μm. This particle size range ensures both the magnetic response speed of the magnetorheological liquid and reduces the particle settling rate.
[0012] In some specific embodiments, the weight ratio of dopamine to carbonyl iron powder in step S2 is 1:(50-200), and the weight ratio of polyisobutylene succinic anhydride to polydopamine-coated carbonyl iron powder is 1:(10-50).
[0013] In some specific embodiments, in step S1, the ultrasonic frequency is 40-60 kHz, and the drying conditions are 70-90°C and vacuum drying for 8-12 hours; in steps S2 and S3, the washing is performed by alternating washing with anhydrous ethanol and deionized water until neutral, and the drying conditions are 70-90°C and vacuum drying for 8-12 hours.
[0014] In some specific embodiments, in step S2, the concentration of the Tris-HCl buffer solution is 0.05-0.15 mol / L, the concentration of the dopamine solution is 1-5 g / L, and the weight ratio of carbonyl iron powder to Tris-HCl buffer solution is 1:(0.5-3); in step S3, the organic solvent is selected from one or more of toluene, xylene, and cyclohexane, and the weight ratio of the polydopamine-coated carbonyl iron powder to the organic solvent is 1:(2-5).
[0015] In some specific embodiments, in step S4, the base liquid and the additive are first mixed and stirred at 800-1000 rpm for 30-180 min to obtain a mixed carrier liquid, and then modified carbonyl iron powder is added for ball milling. During ball milling, the weight ratio of the mixture to the milling media is 1:(1~5). The ball milling is carried out alternately in forward and reverse directions. Each cycle consists of 30 minutes of forward rotation and 30 minutes of reverse rotation, and the cycle is repeated 4 to 6 times.
[0016] In some specific embodiments, the base fluid is selected from one or more of mineral oil, synthetic hydrocarbon oil, synthetic ester oil, silicone oil, vegetable oil, and alcoholic organic compounds.
[0017] In some specific embodiments, the additives include thixotropic agents, anti-wear agents, and antioxidants, with the thixotropic agent content being 1-4%, the anti-wear agent content being 0.5-2%, and the antioxidant content being 0.5-2% based on the total weight of the magnetorheological fluid.
[0018] In some specific embodiments, the thixotropic agent is selected from one or more of polyvinyl alcohol, metal soap, diatomaceous earth, nano-lithium magnesium silicate, and hydrogenated castor oil; the anti-wear agent is selected from one or more of graphite, fluorinated graphite, boron nitride, and organomolybdenum compounds; and the antioxidant is selected from one or more of zinc dialkyl dithiophosphate, zinc dialkyl dithiocarbamate, phosphites, nitrogen-containing heterocyclic compounds, nitrites, and phenolic antioxidants.
[0019] In some specific embodiments, 0.1 to 0.5% of a catalyst is added, wherein the catalyst is one of p-toluenesulfonic acid and concentrated sulfuric acid; the addition of the catalyst can accelerate the grafting reaction rate of polyisobutylene succinic anhydride and polydopamine bridging layer.
[0020] As part of the same inventive concept, this invention also provides a method for preparing the magnetorheological fluid that combines magnetorheological properties and stability, comprising mixing dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder, base liquid and additives, and ball milling at 300-500 rpm for 4-12 hours to obtain the magnetorheological fluid.
[0021] As part of the same inventive concept, this invention also provides the application of the magnetorheological fluid, which combines magnetorheological properties and stability, in vehicle vibration damping systems, precision polishing equipment, and sealing devices.
[0022] Compared with the prior art, the present invention has at least the following advantages: 1) In the magnetorheological fluid provided by the present invention, the strong adhesion of polydopamine is used to achieve a firm bond with the magnetic particle substrate. At the same time, the abundant amino and hydroxyl groups on the surface of polydopamine molecules are used as active sites to achieve stable grafting of polyisobutylene succinic anhydride, forming a core-shell structure modified particle of "magnetic particle substrate - polydopamine bridging layer - polyisobutylene succinic anhydride grafting layer". The two work together to modify carbonyl iron powder, which not only ensures the magnetic properties of the modified particles, but also improves their anti-settling properties. 2) The magnetorheological fluid provided by this invention, wherein the modified dopamine-bridged polyisobutylene succinic anhydride-grafted carbonyl iron powder has excellent hydrophobic properties, is well compatible with the base fluid, and can effectively reduce the density difference between the carbonyl iron powder and the base fluid, thus significantly improving the sedimentation stability of the magnetorheological fluid while maintaining low zero-field viscosity and high shear yield stress. Experiments show that the 30-day sedimentation rate of the magnetorheological fluid is as low as 10%, the zero-field viscosity is ≤500 mPa·s, and the magnetic field strength is 0.8T. The shear yield stress at a certain temperature is ≥70 kPa; that is, the magnetorheological fluid of the present invention, through the synergistic effect of the polydopamine bridging layer and the polyisobutylene succinic anhydride graft layer, constructs a strong "anchoring-steric hindrance" double-layer structure on the surface of magnetic particles; this structure significantly reduces the density difference and interfacial tension between the particles and the carrier fluid, and provides strong steric hindrance, so that the magnetorheological fluid maintains a low zero-field viscosity while having excellent anti-settling properties and high shear yield stress, making it particularly suitable for vehicle vibration damping systems with high requirements for long-term stability. Attached Figure Description
[0023] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.
[0024] Figure 1 This is a schematic diagram of the microstructure of dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder in Example 1 of the present invention. Figure 2 This is a process flow diagram of dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder in Example 1 of the present invention. Figure 3 This is a comparison chart showing the sedimentation rate of the magnetorheological fluids prepared in Examples 1-7 and Comparative Examples 1-6 of the present invention after standing at 20°C for 30 days. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.
[0026] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values listed herein include the endpoints of the range and all integers and fractions within that range.
[0027] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.
[0028] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.
[0029] In the following examples, the carbonyl iron powder used was spherical with an average particle size of 1-10 μm; the dopamine used was dopamine hydrochloride; the polyisobutylene succinic anhydride used had a number average molecular weight of 1000-5000 and a hydrophilic-lipophilic balance value of 3-8; the Tris-HCl buffer solution (0.1 mol / L), the base liquid (synthetic ester oil, brand: Priolube 3970, manufacturer: Croda Chemicals), the thixotropic agent (diatomaceous earth), the anti-wear agent (boron nitride), the antioxidant (zinc dialkyl dithiophosphate), the organic solvent (toluene), and the catalyst (p-toluenesulfonic acid) were all commercially available analytical grade or industrial grade raw materials.
[0030] Example 1
[0031] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. The process flow is as follows: Figure 2 As shown, the specific steps include the following: S1 Surface activation: Take 78g carbonyl iron powder, disperse it in 200mL anhydrous ethanol, sonicate at 40KHz for 20min, magnetically separate it, and vacuum dry it at 80℃ for 10h to obtain surface activated carbonyl iron powder. S2 Polydopamine bridging coating: Prepare 200g of 0.1mol / L Tris-HCl buffer solution, add the surface-activated carbonyl iron powder obtained in step 1), and stir evenly at 800rpm; add 3g / L dopamine solution dropwise until the amount of dopamine is 0.78g (weight ratio of dopamine to carbonyl iron powder 1:100), adjust the pH to 8.5 with sodium hydroxide, and stir the reaction at 25℃ for 20h; after the reaction is completed, perform magnetic separation, wash alternately with anhydrous ethanol and deionized water until neutral, and vacuum dry at 80℃ for 10h to obtain polydopamine-coated carbonyl iron powder; S3 Polyisobutylene succinic anhydride grafting: The polydopamine-coated carbonyl iron powder obtained in step S2 was added to 156g of toluene, along with 3.9g of polyisobutylene succinic anhydride (wherein the number-average molecular weight of polyisobutylene succinic anhydride is 3000, and the hydrophilic-lipophilic balance value is approximately 5.0; the weight ratio of polyisobutylene succinic anhydride to polydopamine-coated carbonyl iron powder is 1:20), and 0.02g of p-toluenesulfonic acid was added as a catalyst. The mixture was stirred at 70℃ for 6h. After the reaction was completed, the mixture was magnetically separated, washed three times with toluene, and vacuum dried at 80℃ for 10h to obtain surface-modified magnetic particles. Preparation of S4 magnetorheological fluid: 17g of synthetic ester oil, 3.0g of diatomaceous earth, 1.0g of boron nitride, and 1.0g of zinc dialkyl dithiophosphate were mixed and stirred at 1000rpm for 60min to obtain a mixed carrier liquid; the surface-modified magnetic particles obtained in step S3 were added, and after being mixed evenly, the mixture was placed in a ball mill jar. Ball milling media were added at a weight ratio of 1:2 between the mixture and stainless steel beads, and the mixture was ball milled at 300rpm for 5h (alternating forward and reverse rotation, 1h per cycle, for a total of 5 cycles). After separation of the ball and liquid, a uniform black magnetorheological fluid was obtained (the microstructure of this rheological fluid is shown in the figure). Figure 1 (As shown).
[0032] Example 2
[0033] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that the ratio of dopamine to polyisobutylene succinic anhydride is different. In step S2, the amount of dopamine used is 0.39g (weight ratio of carbonyl iron powder 1:200); in step S3, the amount of polyisobutylene succinic anhydride used is 1.95g (weight ratio of polydopamine-coated carbonyl iron powder 1:40).
[0034] Example 3
[0035] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that the ratio of dopamine to polyisobutylene succinic anhydride is different. In step S2, the amount of dopamine used is 1.56g (weight ratio of carbonyl iron powder 1:50); in step S3, the amount of polyisobutylene succinic anhydride used is 7.8g (weight ratio of polydopamine-coated carbonyl iron powder 1:10).
[0036] Example 4
[0037] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, the polyisobutylene succinic anhydride used has a number-average molecular weight of 1000 and a hydrophilic-lipophilic balance value of 8.0.
[0038] Example 5
[0039] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, the polyisobutylene succinic anhydride used has a number-average molecular weight of 5000 and a hydrophilic-lipophilic balance value of 3.0.
[0040] Example 6
[0041] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that the base fluid used in step S4 is silicone oil.
[0042] Example 7
[0043] This embodiment provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, no catalyst is added and the grafting reaction time is extended to 8 hours.
[0044] Comparative Example 1 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as Example 1, except that unmodified carbonyl iron powder is directly used as magnetic particles, i.e., steps S1-S3 are omitted.
[0045] Comparative Example 2 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as Example 1, except that the polyisobutylene succinic anhydride grafting in step S3 is omitted, and only the dopamine coating modification in step S2 is performed. That is, the carbonyl iron powder coated with polydopamine obtained in step S2 is used as the magnetic particles.
[0046] Comparative Example 3 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as Example 1, except that step S2, which involves polydopamine interfacial bridging and coating, is omitted. Instead, step S3, which involves grafting polyisobutylene succinic anhydride, is performed directly with the carbonyl iron powder activated in step S1.
[0047] Comparative Example 4 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, sodium dodecylbenzenesulfonate (hydrophilic-lipophilic balance value 10.5) is used instead of polyisobutylene succinic anhydride.
[0048] Test case Referring to the standard method JB / T 12512-2015, the magnetorheological fluids of Examples 1-7 and Comparative Examples 1-6 were subjected to sedimentation rate and magnetorheological performance tests. The test results are listed in Table 1. The sedimentation rate test method is as follows: The magnetorheological fluid is placed in a 25mL graduated cylinder, sealed, and allowed to stand at 25℃ for 30 days. The height of the supernatant is observed at the same time each day. The sedimentation rate is the ratio of the height of the supernatant to the total height. The results are as follows: Figure 3 As shown; The magnetorheological properties test method is as follows: the zero-field viscosity of the magnetorheological fluid at 25℃ and the shear yield stress value under a magnetic field strength of 0.8T are tested on a rheometer. Table 1. 30-day sedimentation rate, zero-field viscosity, and yield stress of the magnetorheological fluids in each embodiment and comparative example.
[0049] Comparative Example 5 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, the polyisobutylene succinic anhydride used has a number-average molecular weight of 800 and a hydrophilic-lipophilic balance value of 8.5.
[0050] Comparative Example 6 This comparative example provides a method for preparing a magnetorheological fluid that combines magnetorheological properties and stability. It is basically the same as that in Example 1, except that in step S3, the polyisobutylene succinic anhydride used has a number-average molecular weight of 6000 and a hydrophilic-lipophilic balance value of 2.6.
[0051] As shown in Table 1, the magnetorheological fluids prepared in Examples 1-7 of this disclosure all exhibited low zero-field viscosity, high shear yield stress, and good sedimentation stability. Among them, Example 1 showed the best overall performance, with a 30-day sedimentation rate of 8%, a zero-field viscosity of 311 mPa·s, and a shear yield stress of 85.2 kPa under a magnetic field strength of 0.8 T. These results indicate that by constructing a composite modified structure on the surface of carbonyl iron powder using a polydopamine bridging layer and a polyisobutylene succinic anhydride graft layer, the interfacial compatibility between magnetic particles and the base fluid can be effectively improved, reducing the tendency for particle agglomeration, thereby achieving a synergistic improvement in sedimentation stability and magnetorheological performance. Compared with Comparative Example 1, the overall performance of Examples 1-7 was significantly improved. Comparative Example 1 used unmodified carbonyl iron powder, which had a 30-day sedimentation rate of 45%, a zero-field viscosity of 1124 mPa·s, and a shear yield stress of only 42.1 kPa. This indicates that the unmodified magnetic particles are prone to aggregation and sedimentation, and are not conducive to the formation of particle chain structure under the action of a magnetic field. Comparative Example 2 was only coated with polydopamine, which had a 30-day sedimentation rate of 35%, a zero-field viscosity of 868 mPa·s, and a shear yield stress of 58.3 kPa. Comparative Example 3 was only modified with polyisobutylene succinic anhydride, which had a 30-day sedimentation rate of 38%, a zero-field viscosity of 795 mPa·s, and a shear yield stress of 57.8 kPa. The above results indicate that neither polydopamine coating alone nor polyisobutylene succinic anhydride modification alone can achieve good stable dispersion. Polydopamine is beneficial for providing interfacial binding sites, while polyisobutylene succinic anhydride plays a steric stabilizing role. The two work together to form a composite modified layer, which is beneficial for improving the overall performance of magnetorheological fluid. Comparative Example 4 uses sodium dodecylbenzenesulfonate instead of polyisobutylene succinic anhydride. Its 30-day sedimentation rate is 36%, its zero-field viscosity is 628 mPa·s, and its shear yield stress is 62.5 kPa. This is because sodium dodecylbenzenesulfonate is a small molecule surfactant and it is difficult to form a stable steric hindrance protective layer. Therefore, its anti-settling performance and magnetorheological properties are lower than those of the technical solution modified with polyisobutylene succinic anhydride.
[0052] Furthermore, the effect of the molecular weight range of polyisobutylene succinic anhydride on performance was investigated through Examples 4 and 5, and Comparative Examples 5 and 6. Examples 4 and 5 used polyisobutylene succinic anhydride with number-average molecular weights of 1000 and 5000, respectively, with 30-day sedimentation rates of 13% and 17%, and shear yield stresses reaching 78.6 kPa and 76.9 kPa, respectively. In contrast, Comparative Example 5 used polyisobutylene succinic anhydride with a number-average molecular weight of 800, resulting in a sedimentation rate of 22%; Comparative Example 6 used polyisobutylene succinic anhydride with a number-average molecular weight of 6000, achieving a sedimentation rate of 24%. The results indicate that when the molecular weight of polyisobutylene succinic anhydride is too low, the steric hindrance layer formed is insufficient; when the molecular weight is too high, the interfacial bonding efficiency and the stability of the modified layer may decrease. Therefore, controlling the number-average molecular weight of polyisobutylene succinic anhydride within the range of 1000–5000 is beneficial for achieving a balance between interfacial bonding ability and steric hindrance effect.
[0053] In addition, Examples 2 and 3 investigated the effect of modifier dosage on performance. In Example 2, reducing the dosage of dopamine and polyisobutylene succinic anhydride increased the sedimentation rate to 15%; in Example 3, increasing the modifier dosage increased the zero-field viscosity to 352 mPa·s, indicating that properly controlling the modified layer thickness and grafting amount is beneficial for obtaining a stable composite interface structure. Example 6 used silicone oil as the base liquid, with a 30-day sedimentation rate of 12%, a zero-field viscosity of 326 mPa·s, and a shear yield stress of 83.7 kPa, indicating that the modified magnetic particles have a certain adaptability to different oil-based base liquids. In Example 7, without adding a catalyst and extending the reaction time, the performance was slightly lower than that of Example 1, indicating that the addition of a catalyst is beneficial for promoting the formation of the composite modified layer.
[0054] In summary, the technical solution disclosed herein utilizes the synergistic effect of polydopamine bridging coating and polyisobutylene succinic anhydride graft modification to form a stable composite modified layer on the surface of carbonyl iron powder, thereby improving the dispersion stability of magnetic particles in the base liquid and maintaining high magnetic response performance. By controlling the number-average molecular weight of polyisobutylene succinic anhydride to 1000–5000, the 30-day sedimentation rate of the magnetorheological fluid is ≤17%, with a minimum of 8%, while also exhibiting low zero-field viscosity and high shear yield stress. This effectively addresses the problem of existing magnetorheological fluids struggling to balance sedimentation stability and magnetorheological performance.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.
Claims
1. A magnetorheological fluid possessing both magnetorheological properties and stability, characterized in that, It comprises the following components by weight percentage: 70-85% dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder, 12-22% base liquid, and 2-9% additives.
2. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 1, characterized in that, The dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder is prepared by the following method: S1. Surface activation: Carbonyl iron powder is dispersed in ethanol, ultrasonically treated for 10-30 min, magnetically separated and dried to obtain surface-activated carbonyl iron powder; S2. Dopamine-bridged coating: The surface-activated carbonyl iron powder in S1 was added to Tris-HCl buffer solution and stirred evenly. Then, dopamine solution was added dropwise to adjust the pH of the system to 8.0-9.
0. The reaction was stirred at 25-35℃ for 12-24 hours. After magnetic separation, washing and drying, polydopamine-coated carbonyl iron powder was obtained. S3. Polyisobutylene succinic anhydride grafting: Polydopamine-coated carbonyl iron powder is added to an organic solvent, followed by polyisobutylene succinic anhydride. The mixture is stirred and reacted at 60–80 °C for 4–8 h. After cooling, the mixture is magnetically separated, washed, and dried to obtain polydopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder.
3. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 2, characterized in that, The polyisobutylene succinic anhydride has a number-average molecular weight of 1000-5000 and a hydrophilic-lipophilic balance value of 3-8; the carbonyl iron powder is spherical with an average particle size of 1-10 μm.
4. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 3, characterized in that, In step S2, the weight ratio of dopamine to carbonyl iron powder is 1:(50-200), and the weight ratio of polyisobutylene succinic anhydride to polydopamine-coated carbonyl iron powder is 1:(10-50).
5. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 1, characterized in that, The base fluid is selected from one or more of the following: mineral oil, synthetic hydrocarbon oil, synthetic ester oil, silicone oil, vegetable oil, and alcoholic organic compounds.
6. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 1, characterized in that, The additives include thixotropic agents, anti-wear agents, and antioxidants. Based on the total weight of the magnetorheological fluid, the thixotropic agent content is 1-4%, the anti-wear agent content is 0.5-2%, and the antioxidant content is 0.5-2%.
7. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 6, characterized in that, The thixotropic agent is selected from one or more of polyvinyl alcohol, metal soap, diatomaceous earth, nano-lithium magnesium silicate, and hydrogenated castor oil; the anti-wear agent is selected from one or more of graphite, fluorinated graphite, boron nitride, and organomolybdenum compounds; the antioxidant is selected from one or more of zinc dialkyl dithiophosphate, zinc dialkyl dithiocarbamate, phosphites, nitrogen-containing heterocyclic compounds, nitrites, and phenolic antioxidants.
8. The magnetorheological fluid possessing both magnetorheological properties and stability according to claim 1, characterized in that, Step S3 also includes adding 0.1-0.5% of a catalyst, wherein the catalyst is one of p-toluenesulfonic acid and concentrated sulfuric acid.
9. A method for preparing a magnetorheological fluid possessing both magnetorheological properties and stability according to any one of claims 1-8, characterized in that, Dopamine-bridged polyisobutylene succinic anhydride grafted modified carbonyl iron powder, base liquid and additives are mixed and ball-milled at 300-500 rpm for 4-12 hours to obtain the magnetorheological fluid.
10. The application of a magnetorheological fluid with both magnetorheological properties and stability according to any one of claims 1-8 in vehicle vibration damping systems, precision polishing equipment, and sealing devices.